Kinetics of CO2 absorption by aqueous 3‐(methylamino)propylamine solutions: Experimental results and modeling. Issue 11 (9th July 2014) - Monteiro, Juliana G. M.‐S.; Hussain, Saddam; Majeed, Hammad; Mba, Emmanuel O.; Hartono, Ardi; Knuutila, Hanna; Svendsen, Hallvard F.
Abstract : Experimental data and a model for the initial kinetics of CO2 into 3‐(methylamino)propylamine (MAPA) solutions are presented in work. MAPA has been tested as an activator for tertiary amines with encouraging results. The measurements were performed in a string of discs contactor and, as no initial kinetics data are available in literature, additional measurements were carried out and in a wetted wall column. The obtained overall mass‐transfer coefficients from both apparatuses are in reasonable agreement. To obtain values for the observed kinetic constant, k obs, the experimental results were interpreted using a two‐film mass‐transfer model and invoking the pseudo‐first order assumption. Needed experimental values for density, viscosity, and Henry's law coefficient for CO2 were measured and are given. The results indicate that MAPA is almost twice as fast as piperazine, eight times faster than 2‐(2‐aminoethyl‐amino)ethanol (AEEA), and 15 times faster than monoethanolamine, when comparing unloaded 1 M solutions at 25°C. The observed kinetic constant was modeled using the direct mechanism. The final expression for k obs can be applied for any concentration and temperature within the experimental data range, and, together with the presented physical data, comprises a complete model for calculating absorption fluxes. © 2014 American Institute of Chemical Engineers AIChE J, 60: 3792–3803, 2014